The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fphar.2022.993927
|View full text |Cite
|
Sign up to set email alerts
|

Potential effects of noni (Morinda citrifolia L.) fruits extract against obsessive-compulsive disorder in marble burying and nestlet shredding behavior mice models

Abstract: Obsessive-compulsive disorder (OCD) is a chronic and complex psychiatric disorder that usually includes both obsessions and compulsions. Morinda citrifolia L. (Noni) is a functional food and it is a well-known plant due to its potential therapeutic effects on human health in many disorders including neurological and neurodegenerative diseases. The purpose of this study was to evaluate the potential effect of M. citrifolia fruits extract (MCFE) against obsessive-compulsive disorder using the marble burying and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Recent studies have suggested that maintaining a proper weight and stable glucose level can help prevent the progression of AD [ 65 , 66 ]. We conducted two types of behavior tests: the marble burying test, known as a test for anxiety, obsessive–compulsive behavior, and repetitive behaviors [ 67 , 68 ], and the nestlet shredding test, known as a test for motivation, psychiatric disorders [ 69 , 70 ], and dopamine-related depressive behaviors [ 71 ] ( Figure 1 D,E). Our data showed that the administration of IGF-1 improved both behavioral assessment scores in the APP/PS2 mice ( Figure 1 D,E).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have suggested that maintaining a proper weight and stable glucose level can help prevent the progression of AD [ 65 , 66 ]. We conducted two types of behavior tests: the marble burying test, known as a test for anxiety, obsessive–compulsive behavior, and repetitive behaviors [ 67 , 68 ], and the nestlet shredding test, known as a test for motivation, psychiatric disorders [ 69 , 70 ], and dopamine-related depressive behaviors [ 71 ] ( Figure 1 D,E). Our data showed that the administration of IGF-1 improved both behavioral assessment scores in the APP/PS2 mice ( Figure 1 D,E).…”
Section: Discussionmentioning
confidence: 99%
“…The test polypropylene cages were kept in a separate room from the housing area. The number of marbles buried at least 2/3 of the way within 30 min was used to measure the compulsive-like digging behavior score [ 67 ]. A score was given when the mice had buried the marbles a distance of 2/3 from the surface into the bedding material [ 134 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nestlet shredding was measured between 12 and 13 mon post-IRR (Fig. 1A) as a complementary method of measuring compulsive-like behaviors (Jeyabalan et al . 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Nestlet shredding was measured between 12 and 13 mon post-IRR (Fig. 1A) as a complementary method of measuring compulsive-like behaviors (Jeyabalan et al 2022). At 20:00, mice were singly housed into identical cages with standard chow and water ad libitum.…”
Section: Nestlet Shredding In a Home Cagementioning
confidence: 99%